EFFECT OF AQ, AO, CA, AND CS ON COMPANY VALUE WITH PROFIT MANAGEMENT AS INTERVENING VARIABLES - Wilsa Road Betterment Sitepu; Dodi Hericho Sinaga; Maslida Bancin (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
This study intends to determine the relationship between audit quality, audit opinion, firm age, firm size on firm value with earnings management as an intervening variable in the Indonesian manufacturing industry. The research method used is associative research method with a quantitative approach. The research population is 112 companies. The sampling technique used is purposive sampling technique. Based on the results of the study, it was confirmed that partially audit quality and company age had a negative and significant effect while audit opinion, firm size had no and no significant effect on earnings management and earnings management had no and no significant effect on firm value for Indonesian manufacturing companies. However, simultaneously audit quality, audit opinion, firm age, firm size have a significant and significant effect on earnings management in Indonesian manufacturing companies.